Focal palmoplantar keratoderma in 2 children leading to gait abnormalities. (2006)
Hereditary focal palmoplantar keratoderma are a heterogeneous group of disorders of keratinization characterized by focal areas of thickening of the palms and soles Different genetic abnormalities have been identified for the disorders under this group. However most of them have palmoplantar keratoderma as a common manifestation. This report is about Nigerian children who presented with focal palmoplantar keratoderma without associated disorders. They presented with gait abnormalities resulting from the plantar hyperkeratosis. One of the children had surgical excision of the lesions with skin grafting, which greatly improved the gait abnormality. Perhaps surgical intervention should be carried out earlier in this group of children in case of absence of other treatment modalities available so as to prevent permanent gait abnormalities. have a similar problem. Examination revealed a young boy with normal scalp hair. His dentition and buccal mucosa were normal. His palms and nails were also found to be normal. The soles of the feet showed bilateral striate hyperkeratosis warty in appearance with well defined edges. Both ankle joints were hyper extended. All other systems were within normal limits. Histology of the excised tissue showed marked hyperkeratosis, acanthosis, hypergranulosis and acanthosis. Histologic features of epidermolytic hyperkeratosis and human papilloma virus were absent. A diagnosis of focal palmoplantar keratoderma without associated features was made, most likely of the striate type. In view of the extent of the lesions and the gait problems. Surgical excision of the hyperkeratosis was suggested. The areas with warty hyperkeratoses were excised bilaterally and skin was taken from the thighs and grafted to the feet. Both grafts healed well. He was then encouraged to bear weight gradually on the graft with the help of physiotherapy. The graft keratinized gradually in the pressure bearing areas and he was adviced to use well padded shoes and take extra care of his feet. He also started physiotherapy to encourage ambulation.